USM WELCOMES MOVE TO RE-ESTABLISH MINISTRY OF HIGHER EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 28 July 2015 Universiti Sains Malaysia (USM) welcomes the move to reestablish the Ministry of Higher Education in the latest Cabinet reshuffle within the Malaysian government. The ViceChancellor of USM, Professor Dato' Dr. Omar Osman said, in facing the various current hurdles, this reestablishment could ensure greater focus being put in pushing the country’s higher education sector further on the international platform.